Mast cell activation mediates blood–brain barrier impairment and cognitive dysfunction in septic mice in a histamine-dependent pathway - Yue, Jianhe; Tan, Ying; Huan, Renzheng; Guo, Jin; Yang, Sha; Deng, Mei; Xiong, Yunbiao; Han, Guoqiang; Liu, Lin; Liu, Jian; Cheng, Yuan; Zha, Yan; et al. (Frontiers in Immunology, 2023)
ABSTRACT Sepsis-associated encephalopathy (SAE) is a diffuse cerebral dysfunction resulting from a systemic inflammatory response to infection; however, its pathophysiology remains unclear. Sepsis-induced neuroinflammation and blood–brain barrier (BBB) disruption are crucial factors in the brain function disturbance in SAE. Mast cells (MCs) activation plays an important role in several neuroinflammation models; however, its role in SAE has not been comprehensively investigated. In this study, we established a SAE model by cecal ligation puncture (CLP) surgery and checked the activation of MCs. By utilizing the MC stabilizer cromolyn, we further analyzed the effects of MCs on neuroinflammation response, BBB permeability and cognitive function, and their underlying molecular mechanism in tissue samples and cellular co-culture system. Results showed that MCs were overactivated in the hippocampus of CLP-induced SAE mice. Cromolyn intracerebroventricular (i.c.v) injection substantially inhibited the MCs activation and neuroinflammation responses, ameliorated BBB impairment, improved the survival rate and alleviated cognitive dysfunction in septic mice. In vitro experiments, we revealed that MC activation increased the sensitivity of brain microvascular endothelial cells (BMVECs) against to lipopolysaccharide (LPS) challenge. Furthermore, we found that histamine/ histamine 1 receptor (H1R) mediated the interaction between MCs and BMVECs, and amplifies the LPS induced inflammation response in BMVECs by modulating the TLR2/4-MAPK signaling pathway. Our results indicated that MC activations could mediate BBB impairment and cognitive dysfunction in septic mice in a histamine-dependent pathway.